PARTISIPASI MASYARAKAT DALAM MEMBAYAR RETRIBUSI KEBERSIHAN DI KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Febrian, Ranggi Ade (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Public Participation levels in paying levies Pekanbaru City Sanitation especially in the village of Simpang Tiga subdistrict Bukit Raya, seen from the first indicator, the level of community participation in pay retribussi hygiene Pekanbaru City with an average value of 56.66% which is included in the category of Medium, then the The second indicator, Changes in people's attitudes become much more concerned about hygiene by paying levies Hygiene with an average value of 29.75% which is included in the low category, then in the third indicator, rate the quality and quantity of input (criticisms and suggestions) for the problem hygiene including levies Hygiene with an average value of 5.5% were categorized as low, and the last or fourth indicator, level of public confidence to the government with an average value of 41.33% which is included in the low category. The main factors that account for the low participation of the community in paying the levy hygiene Pekanbaru City is due to the low awareness of the public to pay the levy hygiene, less optimal implementation of policies concerning levy hygiene and lack of focus of government in addressing the issue of less optimal revenues from reteribusi hygiene this.